2009
DOI: 10.1111/j.1365-2621.2009.02078.x
|View full text |Cite
|
Sign up to set email alerts
|

Gibbs free energy of adhesion of Bacillus cereus isolated from dairy plants on different food processing surfaces evaluated by the hydrophobicity

Abstract: Adhesion of Bacillus cereus A6 and L1, isolated from dairy plants, to stainless steel, granite, and glass surfaces was evaluated. Adhesion of B. cereus to all surfaces was affected by hydrophobicity. Adhesion to the hydrophobic surfaces (DG sws TOT < 0) of granite and stainless steel was greater than adhesion to glass, which was classified as a hydrophilic surface (DG sws TOT > 0). Bacillus cereus A6 adhered in higher numbers to all three surfaces evaluated and was less hydrophilic (DG bwb TOT = 19.83) than B.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…1). Consistent with our data, Araujo et al (Araújo et al, 2009) reported that adherence of B. cereus on any food contact surface is affected by the hydrophobicity and roughness of the surface. The hydrophobicity contributes to adhesion of bacterial cells to surfaces since the water layer on a hydrophobic surface is easily removed owing to the lower interaction between the surface molecules and water molecules (Araújo et al, 2009).…”
Section: Resultssupporting
confidence: 93%
“…1). Consistent with our data, Araujo et al (Araújo et al, 2009) reported that adherence of B. cereus on any food contact surface is affected by the hydrophobicity and roughness of the surface. The hydrophobicity contributes to adhesion of bacterial cells to surfaces since the water layer on a hydrophobic surface is easily removed owing to the lower interaction between the surface molecules and water molecules (Araújo et al, 2009).…”
Section: Resultssupporting
confidence: 93%
“…The most commonly used plastics in packaging industry are based on petrochemical products such as polyethylene terephthalate, polyvinyl chloride, polyethylene, polypropylene, polystyrene, and polyamide (Mahalik and Nambiar, 2010). Surface properties, such as hydrophobicity, roughness, and a predisposition to protein adsorption, are recognized as important for attachment of microorganisms to surfaces and the subsequent biofilm development (Araújo et al, 2009;Palmer et al, 2007). The hydrophobicity of the surfaces contributes to the water removal.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophobicity of the surfaces contributes to the water removal. If two surfaces are hydrophobic, it is easier to eliminate the water layer, because the molecules of surfaces have less attraction to water molecules and higher interaction with themselves (Araújo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…But, what about for biofilms? The physiochemical properties of non-living surface, such as hydrophobicity, roughness, and a predisposition to protein adsorption play generally an important role in attachment of microorganisms to surfaces and the subsequent biofilm development [ 67 ]. Furthermore, adhesion is thermodynamically considered favorable only if the process results in a decrease in total free energy [ 68 ].…”
Section: Discussionmentioning
confidence: 99%